Innovación tecnológica y turismo cultural en la parroquia Cacha, cantón Riobamba, provincia de Chimborazo. - Yánez Calderón, Angel Andrés (2023)
Technology has changed how tourism is experienced and how we relate to cultural heritage, improving accessibility, management, and conservation of cultural tourism. As technological evolution continues, new opportunities are expected to enhance the tourism experience further and preserve cultural heritage. Technological innovation and cultural tourism are mutually beneficial, as technology offers new ways to appreciate and experience cultural heritage. In contrast, cultural tourism provides the context for using technological innovation. This integration has resulted in a new era of cultural tourism that is more interactive, engaging, and accessible. The research methods used were descriptive, documentary, non-experimental, and cross-sectional. The data collection technique used was the survey and the questionnaire as an instrument, which made it possible to obtain detailed information on the subjects' opinions of the study concerning the problem addressed. For selected participants, a nonprobabilistic convenience or intentional sampling was used, which means that those participants who met certain specific characteristics that made them relevant for the study were selected. Finally, through the results of the hypothesis testing, conclusions, and recommendations, the proposal "Design of a web page to promote cultural tourism in the Cacha parish" was designed to benefit the population and the authorities of the Cacha parish.